KONFLIK SOSIAL DALAM DINAMIKA PILKADES DESA KEMBANGAN KECAMATAN BONANG KABUPATEN DEMAK - Nurun Nafiqoh; Kuncoro Bayu Prasetyo (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2025)
The village head election or pilkades is a process of succession of village leadership that is used as a democratic party for the village community to be able to actively participate in determining the government in accordance with the will of the people. Pilkades can have a positive impact on the community, but it is not uncommon for it to cause negative access in the form of conflicts and divisions in the community. The purpose of this study is to determine the background of the conflict in the Pilkades of Kembangan Village, Bonang Subdistrict, Demak Regency and to determine the form of conflict that occurred in the Pilkades of Kembangan Village, Bonang Subdistrict, Demak Regency. This research uses descriptive qualitative research methods with data collection techniques through observation and interviews. The results showed that the conflict occurred suddenly when the community carried out democratic party activities for the election of village head candidates. The causes of the conflict were prejudice between the two candidates, regional differences, the gap between the old and young generations, and the conflict between pro-establishment and pro-change groups. The forms of conflict that occur are realistic and non-realistic conflicts.